Formulation and Evaluation of Lacosamide Loaded Gastro-Retentive Drug Delivery System - Selora Agasti; Romanchak Behura (International Journal of Pharmacy and Analytical Research, 2026)
Lacosamide, an antiepileptic drug, requires sustained release and gastroretentive delivery to improve therapeutic consistency. Floating tablets provide prolonged gastric residence and controlled drug release, enhancing bioavailability. To formulate and evaluate floating tablets of lacosamide using hydrophilic and rate-modifying polymers, optimizing buoyancy and drug release kinetics. Nine formulations (LGT1–LGT9) were prepared employing HPMC K15M and Kollidon SR, selected based on floating lag time and total floating duration results. HPMC K15M was chosen as the primary hydrophilic polymer in line with previous reports. All formulations were subjected to physicochemical evaluation including weight variation, hardness, friability, thickness, and drug content, which were within pharmacopeial limits. Floating parameters such as lag time and total floating time (>8 h) were assessed, and in vitro drug release was carried out in 0.1N HCl for 12 h. Optimized formulations exhibited rapid buoyancy with sustained floating for more than 8 h. The drug release extended up to 12 h, with most batches following zero-order kinetics and demonstrating non-Fickian diffusion. Among the tested formulations, the optimized batch showed desirable floating behavior and controlled release, making it suitable for sustained therapeutic action. Floating tablets of lacosamide formulated with HPMC K15M and Kollidon SR demonstrated robust physicochemical properties, prolonged gastric retention, and sustained drug release up to 12 h. The optimized formulation offers a promising gastroretentive system for enhancing lacosamide bioavailability and patient compliance.